Local innovations to tackling covid-19 in Indonesia: how Depok City government managed the pandemic effectively? - Seftyono, Cahyo; Sari, Prima Karita (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This article examines how locally driven innovations contribute to the effectiveness of decentralization policies, focusing on the COVID-19 pandemic response by the Depok City Government in Indonesia. Using a qualitative case study approach, the research draws on in-depth interviews, field surveys with 932 residents, an online survey of 218 healthcare workers conducted between September 2020 and January 2021, and content analysis of mass and social media conducted in collaboration with citizen experts. The analysis highlights two key initiatives. The first is the COVID-19 Information Center for Depok City (Pusat Informasi COVID-19 Kota Depok), better known as the PICODEP application, which functions as a digital data platform that supports evidence-based policy-making. The second is the Kampung Siaga program, which facilitates community participation in monitoring and managing the local impacts of the pandemic. Despite fiscal and infrastructural constraints, these innovations strengthened Depok’s capacity for timely and effective pandemic control. The study also reveals skepticism among some residents regarding official government assistance. However, it demonstrates that adaptive, collaborative, and inclusive strategies are vital for rebuilding trust and reinforcing local governance. Cross-sector collaboration, including partnerships with academic institutions, together with broad citizen engagement, proved critical for sustainable pandemic adaptation. The integration of technology, grassroots participation, and institutional support not only improved crisis management but also provided valuable lessons for strengthening decentralization frameworks in future emergencies. Ultimately, this article offers a comprehensive analytical perspective on designing adaptive local policies for public health resilience and disaster mitigation.